Garfield assassination engraving cropped - A. Berghaus; C.... (Wikimedia Commons, 1881)
Notice iconographique issue de Wikimedia Commons. Titre: Garfield assassination engraving cropped. An engraving of James A. Garfield's assassination, published in Frank Leslie's Illustrated Newspaper. The caption reads "Washington, D.C.The attack on the President's lifeScene in the ladies' room of the Baltimore and Ohio Railroad depotThe arrest of the assassin / from sketches by our special artist's [sic] A. Berghaus and C. Upham." President Garfield is at center right, leaning after being shot. He is supported by Secretary of State James G. Blaine who wears a light colored top hat. To left, assassin Charles Guiteau is restrained by members of the crowd, one of whom is about to strike him with a cane.
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons